Shrimp waste and marine waste as substitutes of fish meal in broiler diet - Aktar, M; Rashid, M; Azam, MG; Howlider, MAR; Hoque, MA (Bangladesh Journal of Animal Science, 2012)
A total of 192, 14 days old as hatched broilers were fed ad libitum up to 56 days of age, on a control diet with 12% fish meal (FM) and 3 test diets; shrimp waste (SW) and/or marine waste (MW) and equal mixture of SW and MW completely replace dietary FM to have their effects on performance. Live weight and feed conversion improved and feed intake depleted on test diets than that on control. The test diets did not affect survivability of broilers. Complete replacement of FM by SW and/or MW reduced feed cost and production cost with increased profitability of raising broilers. Meat yield decreased on test SM and MW diets, but equal mixture of SM and MW, gave similar meat yield to that on control. It was concluded that equal mixture of SM and MW might be better, economic and efficient substitute of FM. DOI: http://dx.doi.org/10.3329/bjas.v40i1-2.10785 Bang. J. Anim. Sci. 2011. 40 (1-2): 18-22